Unpacking a time interval lengthens its perceived temporal distance - Liu, Yang; Li, Shu; Sun, Yan (Frontiers in Psychology, 2014)
In quantity estimation, people often perceive that the whole is less than the sum of its parts. The current study investigated such an unpacking effect in temporal distance judgment. Our results showed that participants in the unpacked condition judged a given time interval longer than those in the packed condition, even the time interval was kept constant between the two conditions. Furthermore, this unpacking effect persists regardless of the unpacking ways we employed. Results suggest that unpacking a time interval may be a good strategy for lengthening its perceived temporal distance.